If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(3b + -7) = -2b + 30 Reorder the terms: -7(-7 + 3b) = -2b + 30 (-7 * -7 + 3b * -7) = -2b + 30 (49 + -21b) = -2b + 30 Reorder the terms: 49 + -21b = 30 + -2b Solving 49 + -21b = 30 + -2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2b' to each side of the equation. 49 + -21b + 2b = 30 + -2b + 2b Combine like terms: -21b + 2b = -19b 49 + -19b = 30 + -2b + 2b Combine like terms: -2b + 2b = 0 49 + -19b = 30 + 0 49 + -19b = 30 Add '-49' to each side of the equation. 49 + -49 + -19b = 30 + -49 Combine like terms: 49 + -49 = 0 0 + -19b = 30 + -49 -19b = 30 + -49 Combine like terms: 30 + -49 = -19 -19b = -19 Divide each side by '-19'. b = 1 Simplifying b = 1
| 8x^2-2x+4=0 | | [5x-2]=12 | | 8x-6+10x-12=180 | | 8x^2-2x+4=y | | 2m^2-13m+6=0 | | 4(x-4)=5-3x | | x+17=3x-35 | | 11=17-2b | | -33+6b=-(b-2) | | x+9=3x-37 | | 8034*n=80.34 | | 0.5d-0.83d=4 | | 8(7x-1)=64 | | 3x-9=6x+36 | | 4x=(23x+18) | | 12x^2-200=0 | | 14-2x=-5x | | m+4=6.7 | | 3x-11=x+3 | | -5a+6a=56 | | 130=4x+x+120 | | 63x^2-6x-9=0 | | 8a^2(6-3a^2)= | | 6.8-4.2x=5.6x-3 | | 2-2(1-2x)=12(10+x)-3x | | 2+4x+1= | | 3(2+5g)-10=-22+6g | | -3*(h+1.4)=11*(5-h) | | 9x+3x-10=3x+x | | x^2+8x+64= | | -9y=-.162 | | -4(5x-1)=4(-4x-10) |